2022
DOI: 10.1088/1755-1315/1021/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies on the use of surfactant compositions to solve resource extraction problems

Abstract: Based on studies on the interaction and heat resistance of some heat-resistant polymer additives at 128 °C, a sulfonated polyacrylamide polymer AN-125 is proposed as an additive for improving the viscosity of a surfactant composition. The results of experimental studies of a new surfactant composite prepared based on a mixture of ethoxylated and propoxylated sulfate, α-olefin sulfonate and alkylphenol ethoxylate with a concentration of 500 ppm and additives to improve the viscosity in the reservoir model from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The main economic and energy costs during transportation are associated with the operation of pumps and compressors. Therefore, the conducted studies [15] are relevant, the purpose of which was to determine hydraulic losses during the movement of paraffin oil in the pipeline and to identify the influence of temperature on losses. As a result of the study, it was concluded that the hydraulic pressure losses in the oil pipeline depend on the temperature and speed of the pumped liquid.…”
Section: Resultsmentioning
confidence: 99%
“…The main economic and energy costs during transportation are associated with the operation of pumps and compressors. Therefore, the conducted studies [15] are relevant, the purpose of which was to determine hydraulic losses during the movement of paraffin oil in the pipeline and to identify the influence of temperature on losses. As a result of the study, it was concluded that the hydraulic pressure losses in the oil pipeline depend on the temperature and speed of the pumped liquid.…”
Section: Resultsmentioning
confidence: 99%